Rough virulent strain of Brucella ovis induces pro- and anti-inflammatory cytokines in reproductive tissues in experimentally infected rams - Antunes, João Marcelo Azevedo de Paula [UNESP]; Allendorf, Susan Dora [UNESP]; Appolinário, Camila Michele [UNESP]; Cagnini, Didier Quevedo [UNESP]; Figueiredo, Paula Ripamonte [UNESP]; Júnior, José Buratini [UNESP]; Baños, Joaquin Vicente; Kocan, Katherine M.; de la Fuente, José; Megid, Jane [UNESP] (Elsevier, 2013)
The ovine brucellosis caused by Brucella ovis has tropism for reproductive tissues but until now the mechanism of bacterial persistence is not understood. Cytokine expression profiles were studied for 8 months in rams after being experimentally infected with the rough virulent strain of B. ovis (R- B. ovis) to study the pathogenesis of B. ovis and immune mechanism possibly associated to bacteria tropism and persistence. The messenger RNA (mRNA) expression levels of interleukin-1α (IL-1α), IL-1β, IL-6, IL-10, IL-12, interferon-γ (INF-γ) and tumour necrosis factor-α (TNF-α) cytokines were quantified by real-time quantitative RT-PCR (qRT-PCR) in reproductive tissues (epididymus, testicles, ampolae, vesicular glands and bulbourethral glands), and non-reproductive (liver, spleen and kidneys) tissues at 30, 60, 120 and 240 days post infection (dpi). During the acute phase of infection at 30. dpi, the host immune response was most notable demonstrating an up-regulation of several cytokines in reproductive tissues, including the epididymus (IL-6, IL-1β and IL-1α), testicles (INF-γ and IL-12), bulbourethral glands (IL-6 and TNF-α) and ampolae (INF-γ, IL-10, IL-1β and IL-1α). During the development of infection, cytokine gene expression levels decreased, providing evidence of immunosuppression and evidence of immune evasion that favoured persistence of chronic R- B. ovis infection. During the chronic phase of R- B. ovis infection (120 and 240. dpi), cytokine production was down-regulated in the epididymus (IL-1β and IL-1α), testicles (INF-γ and IL-12), and ampolae (INF-γ, IL-10, IL-1β and IL-1α), with the exception of the bulbourethral glands (IL-6 and TNF-α) and epididymus (IL-6); in these tissues, R- B. ovis infection resulted in up-regulation of the pro-inflammatory cytokine IL-6. Herein, we report cytokine expression profiles in tissues of rams experimentally infected with the rough strain of B. ovis, which are associated with bacterial persistence and macrophage activation. © 2012 Elsevier B.V.
Keywords: Brucella ovis; Brucellosis; Cytokines; Gene expression; Ram; Rough strain; cytokine; gamma interferon; interleukin 10; interleukin 12; interleukin 1alpha; interleukin 1beta; interleukin 6; messenger RNA; tumor necrosis factor alpha; ampolae; animal experiment; animal tissue; bacterial strain; bacterial virulence; brucellosis; bulbourethral gland; controlled study; epididymis; experimental infection; gene expression; genital system; immune deficiency; immune evasion; immune response; kidney; liver; nonhuman; protein blood level; quantitative analysis; ram (sheep); real time polymerase chain reaction; sheep disease; spleen; testis; tropism; vesicular gland; Animals; Genitalia, Male; Inflammation; Macrophage Activation; Male; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sheep; Sheep Diseases; Up-Regulation; Bacteria (microorganisms); Brucella melitensis biovar Ovis; Ovis